2017
DOI: 10.1371/journal.pone.0174097
|View full text |Cite
|
Sign up to set email alerts
|

Measuring mortality due to HIV-associated tuberculosis among adults in South Africa: Comparing verbal autopsy, minimally-invasive autopsy, and research data

Abstract: BackgroundThe World Health Organization (WHO) aims to reduce tuberculosis (TB) deaths by 95% by 2035; tracking progress requires accurate measurement of TB mortality. International Classification of Diseases (ICD) codes do not differentiate between HIV-associated TB and HIV more generally. Verbal autopsy (VA) is used to estimate cause of death (CoD) patterns but has mostly been validated against a suboptimal gold standard for HIV and TB. This study, conducted among HIV-positive adults, aimed to estimate the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…Only one study, conducted by our group in South Africa, has compared VA to CoD derived from pathological autopsy in HIV-positive individuals and found that VA methods likely underestimated HIV-associated CoD. 29 In part because of difficulties faced with ICD coding, there are few direct (autopsy or clinical) estimates of the HIV-associated mortality fraction among HIV-positive adults. A recent systematic review, which included only studies of HIV-positive individuals entirely or mostly on ART (n=19 studies), estimated that 18.5% (95% CI 13 to 24) of deaths in HIV-positive individuals on ART in sub-Saharan countries were due to ‘non-AIDS’ causes (ie, 76%–83% due to AIDS).…”
Section: Discussionmentioning
confidence: 99%
“…Only one study, conducted by our group in South Africa, has compared VA to CoD derived from pathological autopsy in HIV-positive individuals and found that VA methods likely underestimated HIV-associated CoD. 29 In part because of difficulties faced with ICD coding, there are few direct (autopsy or clinical) estimates of the HIV-associated mortality fraction among HIV-positive adults. A recent systematic review, which included only studies of HIV-positive individuals entirely or mostly on ART (n=19 studies), estimated that 18.5% (95% CI 13 to 24) of deaths in HIV-positive individuals on ART in sub-Saharan countries were due to ‘non-AIDS’ causes (ie, 76%–83% due to AIDS).…”
Section: Discussionmentioning
confidence: 99%
“…The MIA is a protocolized and systematic post-mortem methodology targeting key organs (brain, lungs, heart, liver, spleen, kidneys, bone marrow, uterus) and bodily fluids (blood and cerebrospinal fluid), and aiming to provide sufficiently good quality samples for pathological and microbiological investigations so as to substitute the complete pathological autopsy. The MIA has been validated for CoD investigation in all age groups [11][12][13][14] and has been used in different settings [15,16]. CoD results derived from the use of the MIA tool could also contribute in the future to modify and improve current analytical approaches utilized for VA data interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…Another prospective study in Zambia found that in those inpatients without presumptive TB (i.e. without presence of cough of 2 or more weeks at admission) but who were able to provide a sputum sample, 19/133 (14.3%) were HIV-positive and 7/118 (5.9%) had culture-confirmed TB 10 . Thus, given the low case detection rate in the Mozambique and the lack of active case finding strategies during the study period, misdiagnosis could have been due to poor diagnostic work-up and the intrinsic challenges to diagnose TB in HIV-positive patients, who are frequently paucibacillary and often asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the increased mortality associated with TB misdiagnosis, in particular, with TB underdiagnosis 8 , 9 . Although TB is a common cause of death in post-mortem studies conducted in high HIV prevalence settings 10 13 , ascertainment of TB as a cause of death is challenging in most low income countries 14 16 . In addition, PLHIV with clinically diagnosed TB have a higher mortality risk than those with laboratory-confirmed TB 17 highlighting the importance of improving laboratory-based TB diagnosis in this population.…”
Section: Introductionmentioning
confidence: 99%